Geochemistry of elements associated with Late Permian coal in the Zhongliangshan mine, Chongqing, Southwest China. Issue 6 (November 2018) - Qin, Shenjun; Lu, Qingfeng; Gao, Kang; Bo, Penghui; Wu, Shihao
The enrichment and geochemical significance of elements associated with Late Permian coals in Southwest China have always gained widespread interest in the field of coal geology. The present study focuses on the geochemical characterization of Late Permian coal in the Zhongliangshan mine. Twenty-three samples were collected from the K1a coal seam of the Zhongliangshan mine, and the major and trace elements in the coal were analyzed by using X-ray fluorescence spectroscopy (XRF) and inductively coupled plasma mass spectrometry. The composition of minerals in the Zhongliangshan coal, and the modes of occurrence of coal-associated elements, especially those with elevated contents, were studied through a combination of microscopic analyses, X-ray powder diffraction, and scanning electron microscope – energy dispersive X-ray spectrometer. The minerals in coal mainly consist of kaolinite, pyrite, calcite, and quartz, as well as small amount of gypsum and anatase. Compared with the average elemental concentrations in world coal, the Zhongliangshan coal is enriched in Cr, and slightly enriched in Li, U, Sr, V and Ag. Combining the correlation analysis and sequential chemical extraction experiments, it can be inferred that many trace elements in the Zhongliangshan coal have both inorganic and organic affinities. The elements Cr, Li, and V mainly occur in clay minerals, and also are related to organic matter in the coal. Uranium presents firstly in the organic and then silicate states. Strontium shows multiple modes of occurrence including carbonate, silicate, and exchangeable ion states, and Ag primarily occurs in sulfides followed by silicates. The terrigenous debris input from the Emeishan basalt is the major reason for the enrichment of above elements in the Zhongliangshan coal.